Intertemporal Choice Behavior in Emerging Adults and Adults: Effects of Age Interact with Alcohol Use and Family History Status - Smith, Christopher T.; Steel, Eleanor A.; Parrish, Michael H.; Kelm, Mary K.; Boettiger, Charlotte A. (Frontiers in Human Neuroscience, 2015)
Adults with alcohol use disorders (AUDs) show marked immediate reward selection (or “Now”) bias in intertemporal choice tasks. This Now bias persists long into abstinence, suggesting an irreversible consequence of chronic alcohol abuse or a pre-existing AUD intermediate phenotype. However, some data show substantial Now bias among emerging adults (18–25), regardless of drinking behavior, suggesting age-dependent effects on Now bias. The objectives of the present study were to determine (1) whether Now bias is greater among emerging adults relative to adults, (2) whether any such age effect on Now bias is diminished in sub-clinical heavy alcohol users, and (3) whether having a problem drinking first degree relative is independently associated with elevated Now bias. To achieve these objectives, we used an intertemporal choice task to quantify Now bias in n = 237 healthy participants (ages 18–40; 50% female), and a wide range of non-zero alcohol use, based on the Alcohol Use Disorders Identification Test (AUDIT). We found that among non-heavy drinkers, Now bias inversely correlated with age; this relationship was not present among heavy drinkers. We found no significant relationship between AUDIT score and Now bias among emerging adults, but AUDIT scores and Now bias were positively correlated among 26–40 year olds. Additionally, non-heavy drinking adults who reported a problem drinking first degree relative showed greater Now bias compared to those not reporting familial problem drinking. While not definitive, these findings lend support for elevated Now bias in adulthood as an intermediate phenotype for AUDs. Moreover, non-additive effects of age and heavy drinking on Now bias suggest perturbations in largely common neural circuits in both groups.